Astaxanthin Based Indicator For Light Metals In Haematococcus pluvialis - Fan, Wei Jiong (2017)
Pollution of heavy metal was concerned as a critical and crucial issue with regards to environment biotechnology and agriculture biotechnology. A high concentration of heavy metal had been acknowledged as toxic for all organisms. In this case, toxicity of chromium would inhibit ion of enzymatic activity, carcinogenic and so on. However, due to being the highest contribution in earth crust, aluminium (Al) had become another main study for pollution problem. Therefore for my study, mycoremediation would be used to reduce the heavy metal contamination from soil and environment. Therefore, P. ostreatus was decided to be used to remove the heavy metal. The focus of my study was to determine the effect of chromium and aluminium on the growth of P. ostreatus as well as the effect of pH values on the growth of P. ostreatus. In this case, the mycelium of P. ostreatus would be cultured on potato dextrose agar (PDA) medium and the parameters involved were the different concentrations of Aluminum (Al) and Chromium (Cr) in different pH values. The optimum Cr and Al concentration for growth of P. ostreatus were found to be 40 mg/L and 120 mg/L respectively. On the other hand, the optimum pH value for growth of P. ostreatus in this research was pH 7 and pH 6 for both Cr and Al supplemented PDA media.